Discomfort in Ian McEwan’s The Comfort of Strangers - Mohammad Jibraan Fazili; Aadil Zeffer (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper aims to study the discomfort experienced by characters in Ian McEwan’s (1948-Present) novel, The Comfort of Strangers (1981). In the novel, the whole scenario presents a bleak picture before the readers and one can easily guess that the things are going in a horrible direction. The paper further studies that in the contemporary milieu, the anguish, cruelty, selfishness, discomfort, decomposition and death has spread everywhere. The life has lost meaning in its true sense and every entity of the planet seems at stake. McEwan explores the world of crisis and its persistent effect on contemporary society.